Carbon productivity and volatility - Jung, Hail; Lee, Junyoup; Song, Chang Keun (Finance Research Letters, 2023)
This study investigates the relationship between firm-level carbon productivity and volatility. With increasing interest in sustainable investing and inclusion of carbon productivity in financial assessments, we examine whether the market considers firms with high carbon productivity as less risky. Using U.S. firm-level carbon emission data, we find that carbon productivity is negatively associated with total and idiosyncratic volatilities. Our main findings hold under propensity score matching and coarsened exact matching. We also show that this relationship is significant when the binding intergovernmental regulations such as the Paris Agreement is active.
Keywords: Carbon productivity; Climate change; ESG; Risk; Volatility